LA “PREVIA DEPORTIVA” COMO GÉNERO PERIODÍSTICO. UNA MIRADA DESDE EL ÁMBITO PROFESIONAL - Dra. Aránzazu ROMÁN SAN MIGUEL (Fonseca, Journal of Communication, 2023)
Sport previous is an independent journalistic genre into the Sport Journalism, where more force has this way of telling the reality. Little has been studied about this journalistic genre and, sometimes, it is approached from the point of view of chronic or without even bring anything new on it.Some authors as Dr. Aránzazu Román have already addressed this genre differentiating it from other with which it has traditionally been confused as chronic or news.